IMPLEMENTATION OF E-GOVERNMENT AS AN EFFORT TO SUPPORT THE BUREAUCRACY REFORM OF GOVERNMENT INSTITUTIONS - Paramitha, Pinastika Prajna (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2025)
EMIS (Education Management Information System) is an appropriate administrative method in providing good and usable learning data so that the direction, preparation, project improvement, and Education management functions can be carried out effectively. In another sense, EMIS is the coordinated collection of data and documentation in completing the selection, storage, handling, inspection, and dissemination of data used for education planning. EMIS systems are used to organize a wealth of instructive information and data that can be read, recovered, handled, investigated, introduced and disseminated. We have now entered the era of society 5.0, where all activities have begun to use technology to consider aspects of the humanities in the process of solving public sector problems. Therefore, in this study, the aim is to determine the strengthening of bureaucratic reform into the era of society 5.0 by managing human resource development planning for the Ministry of Administrative Reform and Bureaucratic Reform (KemenPANRB). The method used for this analysis is observation and literature study, which is the same as other research, but the sources and methods of collecting data are by interviewing the Malang Regency Ministry of Religion and taking data in the library, reading, recording and researching research data